SCIENTIFIC DISCUSSION ON THE ESSENCE OF STATE FINANCIAL REGULATION IN MODERN CONDITIONS - M. L. Dorofeev (Вестник университета)
There is no doubt that the role of the state and its regulatory intervention in the economy in the era of regulated market economy is very high, since it allows us to overcome unprecedented challenges such as the COVID-19 pandemic in 2020. The article analyses the concept of state financial regulation in modern conditions on the basis of various Russian and foreign sources. A review of scientific literature showed that this concept is interpreted differently and, in general, opinions can be combined into two groups: a scientific school that believes that financial regulation is the prerogative of fiscal authorities and manifests itself in the budgetary process; a scientific school that considers this process as the actions of a prudential regulator responsible for the stability of the financial system and the banking sector of the economy. The result of the research paper are the analysis of the causes of differences in opinions and the suggests to eliminate existing contradictions in the form of text, graphical and classificational definitions of the concept under study – government financial  regulation.